2010
DOI: 10.1523/jneurosci.1425-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Presynaptic Calcium and Synaptic Plasticity in a Mouse Model of 22q11 Deletion Syndrome

Abstract: The 22q11 deletion syndrome (22q11DS) is characterized by cognitive decline and increased risk of psychiatric disorders, mainly schizophrenia. The molecular mechanisms of neuronal dysfunction in cognitive symptoms of 22q11DS are poorly understood. Here, we report that a mouse model of 22q11DS, the Df(16)1/؉ mouse, exhibits substantially enhanced short-and long-term synaptic plasticity at hippocampal CA3-CA1 synapses, which coincides with deficits in hippocampus-dependent spatial memory. These changes are evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 69 publications
10
104
2
Order By: Relevance
“…Consistent with this concept, mounting evidence from gene profiling, genetic association, and proteomic analyses indicates that alterations in presynaptic function contribute to the etiology of schizophrenia (Chen et al, 2004;Lee et al, 2005;Behan et al, 2009;Maycox et al, 2009;Faludi and Mirnics, 2011). In addition, several studies have reported alterations in presynaptic function or short-term synaptic plasticity in other mouse models of schizophrenia (Jentsch et al, 2009;Talbot, 2009;Blundell et al, 2010;Earls et al, 2010;Kvajo et al, 2011). Critically, our study extends on these findings by revealing an integrated disease mechanism that links presynaptic dysfunction with corresponding effects on higher-order circuit, network, and cognitive functions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Consistent with this concept, mounting evidence from gene profiling, genetic association, and proteomic analyses indicates that alterations in presynaptic function contribute to the etiology of schizophrenia (Chen et al, 2004;Lee et al, 2005;Behan et al, 2009;Maycox et al, 2009;Faludi and Mirnics, 2011). In addition, several studies have reported alterations in presynaptic function or short-term synaptic plasticity in other mouse models of schizophrenia (Jentsch et al, 2009;Talbot, 2009;Blundell et al, 2010;Earls et al, 2010;Kvajo et al, 2011). Critically, our study extends on these findings by revealing an integrated disease mechanism that links presynaptic dysfunction with corresponding effects on higher-order circuit, network, and cognitive functions.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, we show that calcineurin deficiency results in a gene dose-dependent impairment of performance in a DNMTP operant working memory task. Last, we provide evidence that a similar alteration in synaptic vesicle cycling may occur in the PFC of schizophrenia patients as a consequence of reduced expression of the presynaptic protein and calcineurin substrate, dynamin I, which has been shown to be specifically required for sustaining high-frequency neuronal firing (Ferguson et al, 2007). Based on these data, we propose a presynaptic mechanistic framework for working memory dysfunction in the context of schizophrenia (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These deficits were also observed in primary cultures from Zdhhc8-deficient mice and could be prevented by introduction of enzymatically active ZDHHC8 palmitoyltransferase. However, these structural changes were not replicated in Df1(16)1/+ mice (Earls et al 2010). Using this model, Earls et al (Earls et al 2010) reported deficits in spatial memory associated with increased long term potentiation and enhanced pre-synaptic glutamate release in hippocampal CA3-CA1 pyramidal neurons.…”
Section: The Mouse As a Model For Dissecting The 22q112 Chromosomal mentioning
confidence: 98%
“…22,23 Surgery was performed over the auditory cortex, and cranial windows were installed as described under "Intravital fluorescence microscopy." Rhodamine-dextran (10 000 MW, 1 mg/mouse; Invitrogen) was injected to visualize the vasculature along with the GFP neutrophils.…”
Section: In Vivo 2-photon Imagingmentioning
confidence: 99%